Training in Temporal Information Processing Ameliorates Phonetic Identification - Szymaszek, Aneta; Dacewicz, Anna; Urban, Paulina; Szelag, Elzbieta (Frontiers in Human Neuroscience, 2018)
Many studies revealed a link between Temporal Information Processing (TIP) in a millisecond range and speech perception. Previous studies indicated a dysfunction in TIP accompanied by deficient phonemic hearing in children with Specific Language Impairment (SLI). In this study we concentrate in SLI on phonetic identification, using the Voice-Onset-Time (VOT) phenomenon in which TIP is built-in. VOT is crucial for speech perception, as stop consonants (like /t/ vs. /d/) may be distinguished by an acoustic difference in time between the onsets of the consonant (stop release burst) and the following vibration of vocal folds (voicing). In healthy subjects two categories (voiced and unvoiced) are determined using VOT task. The present study aimed at verifying whether children with SLI indicate a similar pattern of phonetic identification as their healthy peers and whether the intervention based on TIP results in improved performance on the VOT task. Children aged from 5 to 8 years (n=47) were assigned into two groups: normal children without any language disability (NC, n=20), and children with SLI (n=27). In the latter group participants were randomly classified into 2 treatment subgroups, i.e., experimental temporal training (EG, n=14) and control non-temporal training (CG, n=13). The analysed indicators of phonetic identification were: (1) the boundary location (α) determined as the VOT value corresponding to 50% voicing/unvoicing distinctions; (2) ranges of voiced/unvoiced categories; (3) the slope of identification curve (β) reflecting the identification correctness; (4) percent of voiced distinctions within the applied VOT spectrum. The results indicated similar α values and similar ranges of voiced/unvoiced categories between SLI and NC. However, β in SLI was significantly higher than that in NC. After the intervention, the significant improvement of β was observed only in EG. They achieved the level of performance comparable to that observed in NC. The training-related improvement in CG was nonsignificant. Furthermore, only in EG the β values in post-test correlated with measures of TIP as well as with phonemic hearing obtained in our previous studies. These findings provide another evidence that TIP is omnipresent in language communication and reflected not only in phonemic hearing but also in phonetic identification.